Superinfection is associated with short-term outcome and mortality in viral respiratory tract infections during the fall-winter seasons 2016-2018 in the Greater Paris area: the SUPERFLUOUS study: outcomes of viral infections. (June 2022) - Davido, Benjamin; Lemarie, Benoit; Gault, Elyanne; Pepin, Marion; Jaffal, Karim; Beaune, Sebastien; Dahmane, Lotfi; Dumoulin, Jennifer; Greffe, Segolene; Annane, Djillali; De Truchis, Pierre
Highlights: Outcome of viral respiratory tract infections is closely related to superinfections. Better use of antibiotics requires routine molecular testing. Extending vaccination coverage in patients at risk is essential to limit mortality. ABSTRACT: Background: Following a study of predictors of superinfection in viral respiratory tract infections (VRTIs), this study analyzes the predictors of the outcome. Methods: Multicenter retrospective study conducted among adults who tested positive for VRTIs with reverse-transcription polymerase chain reaction. We compared characteristics between influenza virus, Paramyxoviridae, and Pneumoviridae and identified predictors of favorable short-term outcome, admission to the intensive care unit (ICU), and mortality. Results: A total of 590 patients had VRTI, including 347 (59%) influenza infections. Mean (SD) patient age was 71.0 (18.3) years, with a sex ratio of 0.91. In multivariate analyses, predictors of favorable short-term outcome were age ≤75 years (adjusted odds ratio [aOR] 5.38 [95% confidence interval, 1.59-18.2]), absence of respiratory disease (4.94 [1.01-24.37]), and absence of superinfection (aOR 3.91 [1.37-11.13]). The predictors of ICU admission were age ≤75 years (aOR 3.28 [1.71-6.25]), chronic respiratory disease (aOR 2.49 [1.20-5.19]), and procalcitonin level >0.25 ng/mL (aOR 4.25 [1.55-11.67]). Predictors of mortality were use of inhaled corticosteroids (2.49 [1.10-5.63]), influenza infection (2.73 [1.27-5.85]), Charlson score ≥5 (5.35 [1.90-15.05]), superinfection (2.54 [1.05-6.18]), and eosinophil count <50/µL (4.39 [1.19-16.2]). Certainty of superinfection was significantly associated with mortality (2.23 [1.15-4.3]). Conclusion: Our study revealed that superinfection was significantly related to the outcome, and that virus species affects mortality. These findings emphasize the need for improving the tools used in daily practice to confirm certainty of superinfection and for broader implementation of vaccination of individuals at risk of VRTIs.